How Gig Worker Responds to Negative Customer Treatment: The Effects of Work Meaningfulness and Traits of Psychological Resilience - Xiongtao, He; Wenzhu, Lu; Haibin, Luo; Shanshi, Liu (Frontiers in Psychology, 2021)
The negative interpersonal interaction between customers and platform gig workers has become a problem for platform owners and government. This study investigates the role of negative customer treatment in the context of gig work and its impact on gig workers’ sabotage behavior. A questionnaire survey approach was used in the study, collected three-wave survey data from 258 Chinese gig workers including food-deliver platform workers and app-based ride-hailing drivers. Both effects of the mediation and moderation were tested, all of which find support, using hierarchical multiple regression by SPSS22.0. Results indicate that negative customer treatment can also predict gig workers’ service sabotage through work meaningfulness. Furthermore, positive customer treatment acted as an effective safeguard against the effects of negative customer treatment on employee service sabotage. Trait psychological resilience can also mitigate the effects of a low level of work meaningfulness. The manuscript’s focus provides an interesting angle to the previous research, especially the inclusion of work meaningfulness and trait resilience, on negative customer treatment in the context of gig work. This study contributes to further broaden the perspective of conservation of resource (COR) theory for individual intrinsic motivation analysis. Practical implications for platform management and government governance have also been discussed in this manuscript.